Mitochondria-Targeted Lipid Nanoparticles Loaded with Rotenone as a New Approach for the Treatment of Oncological Diseases - Leysan Vasileva; Gulnara Gaynanova; Darya Kuznetsova; Farida Valeeva; Anna Lyubina; Syumbelya Amerhanova; Alexandra Voloshina; Guzel Sibgatullina; Dmitry Samigullin; Konstantin Petrov; Lucia Zakharova (Molecules, 2023)
This research is based on the concept that mitochondria are a promising target for anticancer therapy, including thatassociated with the use of oxidative phosphorylation blockers (mitochondrial poisons). Liposomes based on L-α-phosphatidylcholine (PC) and cholesterol (Chol) modified with cationic surfactants with triphenylphosphonium (TPPB-n, where n = 10, 12, 14, and 16) and imidazolium (IA-n(OH), where n = 10, 12, 14, and 16) head groups were obtained. The physicochemical characteristics of liposomes at different surfactant/lipid molar ratios were determined by dynamic/electrophoretic light scattering, transmission electron microscopy, and spectrophotometry. The hydrodynamic diameter of all the systems was within 120 nm with a polydispersity index of no more than 0.24 even after 2 months of storage. It was shown that cationization of liposomes leads to an increase in the internalization of nanocontainers in pancreatic carcinoma (PANC-1) and duodenal adenocarcinoma (HuTu 80) cells compared with unmodified liposomes. Also, using confocal microscopy, it was shown that liposomes modified with TPPB-14 and IA-14(OH) statistically better colocalize with the mitochondria of tumor cells compared with unmodified ones. At the next stage, the mitochondrial poison rotenone (ROT) was loaded into cationic liposomes. It was shown that the optimal loading concentration of ROT is 0.1 mg/mL. The Korsmeyer–Peppas and Higuchi kinetic models were used to describe the release mechanism of ROT from liposomes in vitro. A significant reduction in the IC50 value for the modified liposomes compared with free ROT was shown and, importantly, a higher degree of selectivity for the HuTu 80 cell line compared with the normal cells (SI value is 307 and 113 for PC/Chol/TPPB-14/ROT and PC/Chol/IA-14(OH)/ROT, respectively) occurred. It was shown that the treatment of HuTu 80 cells with ROT-loaded cationic liposomal formulations leads to a dose-dependent decrease in the mitochondrial membrane potential.